Pelatihan Kompetensi Keahlian Pada Siswa SMKN 1 Pringgasela - Hidayat, Muh. Adrian Juniarta; Putra, Yupi Kuspandi; Fathurrahman; Muhammad Saiful; L.M.Syamsu; Sutriandi, Aswian Editri (Universitas Hamzanwadi, 2024)
This service aims to help students improve their readiness and skills in completing the Software Engineering Competency Test. Currently, the national exam is no longer a determinant of vocational high school student graduation based on government regulations through the Ministry of Education and Culture which regulates policies and criteria for student graduation. The school has full authority to determine the graduation requirements for its students, but these requirements must be in accordance with the circular issued by the Government. The target of this activity is students of SMKN 1 Pringgasela who are the main partners. The target and output of this activity is to increase skills in working on competency test questions. The method used is Participatory Learning and Action (PLA). This activity is carried out by providing knowledge and skills in theory and practice. With the training of competency skills, especially in the field of Software Engineering, it is hoped that it can help students prepare for the competency test to get maximum results and improve student competence